Di Balik Teluk Balikpapan: Framing Eksploitasi Korporasi pada Film Dokumenter Gone with The Tide dan Into The Shadow - Rini Asmiyati; Sumekar Tanjung (Fakultas Ilmu Komunikasi UKWMS, 2021)
This study aims to explain the framing of corporate exploitation of fishermen's life and natural damage in Balikpapan Bay through the documentary films Gone with The Tide and Into The Shadow. Corporate exploitation activities are a major source of problems in Balikpapan Bay. Expansive corporate growth but not followed by efforts to save nature is the main highlight of this second film. The choice of research object takes into consideration the function of documentary films as a medium of criticism and awareness to the public. In addition, Gone with The Tide and Into The Shadow present the problems of Balikpapan Bay based on the same director's point of view. The researcher uses the Pan & Kosicki framing method to explain the framing of corporate exploitation through 16 scenes in the second film. Researchers found seven constructions formed in this film, namely, the allusion to the provincial and central government, Balikpapan Bay is a strategic area, cornering the Kariangau Industrial Area, lack of attention to fishermen's welfare, maintaining a balance between industrial and environmental activities, cornering corporate and government over endangerment of marine mammals. Although it does not necessarily change people's awareness, documentary films have provided inspiration for environmental changes.Penelitian ini bertujuan menjelaskan pembingkaian eksploitasi korporasi terhadap Teluk Balikpapan melalui film dokumenter Gone with The Tide dan Into The Shadow. Kegiatan eksploitasi korporasi menjadi sumber utama masalah di Teluk Balikpapan. Pertumbuhan korporasi yang ekspansif namun tidak diikuti dengan upaya penyelamatan alam menjadi sorotan utama kedua film ini. Pemilihan objek penelitian berdasarkan pertimbangan fungsi film dokumenter sebagai medium kritik dan penyadaran kepada masyarakat. Selain itu, Gone with The Tide dan Into The Shadow menyajikan permasalahan Teluk Balikpapan berdasarkan sudut pandang sutradara yang sama. Peneliti menggunakan metode framing Pan & Kosicki untuk menjelaskan pembingkaian eksploitasi korporasi melalui 16 scene dalam kedua film. Peneliti menemukan tujuh konstruksi yang terbentuk dalam film ini yaitu, sindiran bagi pemerintah provinsi dan pusat, Teluk Balikpapan merupakan kawasan strategis, menyudutkan Kawasan Industri Kariangau, kurangnya perhatian atas kesejahteraan nelayan, pentingnya keseimbangan antara kegiatan industri dan lingkungan, menyudutkan pihak korporat, dan kekhawatiran atas terancamnya mamalia laut. Meski tidak serta merta mengubah kesadaran masyarakat, namun film dokumenter telah memberikan inspirasi bagi perubahan lingkungan.